The Jefferson Bible: a biography - Manseau, Peter (Lives of great religious books, 2020)
Cover -- Title -- Copyright -- CONTENTS -- LIST OF ILLUSTRATIONS -- AUTHOR'S NOTE AND ACKNOWLEDGMENTS -- INTRODUCTION Excavating the Sacred -- CHAPTER 1 Sharpening the Blade -- CHAPTER 2 Making the Cut -- CHAPTER 3 The Quest for the Jeffersonian Jesus -- CHAPTER 4 Lost and Found -- CHAPTER 5 Born Again -- CHAPTER 6 Social Engineering -- CHAPTER 7 Congressional Inheritances -- CHAPTER 8 Jefferson, Jesus, and the Sixties -- CHAPTER 9 Choose Your Own Adventure -- EPILOGUE Bible as Barrow -- ILLUSTRATIONS -- NOTES -- INDEX.